MODIFICATION OF GUMS BY PERIODATE OXIDATION: A NATURAL CROSS-LINKER - Sen, Suma Oommen; Nayak, Amit Kumar; Devbhuti, Pritesh; Ghosh, Amitava (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Scientists throughout the world are in search of novel modified biopolymer to fabricate smart drug delivery systems based on hydrogel formulations using several cross-linkers like glutaraldehyde, glyoxal, epichlorhydrin, adipic acid dihydrazide, carbodiimide, genipin, etc. Agents that are fused into the polymeric structure like isocyanates, glutaraldehyde, polyepoxides, etc., and are extremely toxic in nature. In addition, these are susceptible to percolate out into the body on biodegradation of polymeric structure. As an alternative to these toxic cross-linking agents, the periodate-Schiff base staining technique is widely being used for cross-linking in biology and biochemistry. The mechanism of this cross-linking technique is based on the reaction in-between the Schiff reagent and the aldehydes produced via the periodate oxidation. During the past few decades, several researchers have already been studied on the natural gums and also, developed their dialdehyde derivatives via the periodate oxidation technique. These periodate oxidized gums are being used to cross-link gelatin, other proteins and chitosan to develop various smart systems for drug delivery, tissue engineering, wound dressing, edible films, etc. The current review presents a comprehensive discussion of the available reported literature on the periodate oxidation of various gums and their use as natural cross-linker.